Maximizing the Response of SPR Signal: A Vital Role of Light Excitation Wavelength - Mukhtar, WM; Murat, NF; Samsuri, ND; Dasuki, KA (Amer Inst Physics, 2024)
Criteria for development of high sensitivity surface plasmon resonance (SPR) sensor depends on several factors such as types of metals, light polarization modes, light coupling techniques and thicknesses of metal film. This paper discussed the effect of light excitation wavelength ranging from ultra violet (UV) region to infrared (IR) region on SPR. Three regions have been classified such as UV region (from lambda=200nm to lambda 380nm), visible region (from lambda=400nm to lambda=633nm) and IR region (from lambda=870nm to lambda=1550nm). Noble metal gold thin film with thickness of 50nm and refractive index of n=0.1759+3.3104k was deposited on top of BK7 triangular prism (n=1.51). Very weak SPR signal was generated as the excitation wavelength was set in UV region. The signal's strength increased about 26.63% with the increment of wavelength from lambda=200nm until lambda=380nm, resulting the blue-shifting of SPR angle from 54.03 degrees to 43.48 degrees. The greatest excitation of SPP was significantly observed as the visible light region was incident through the thin film gold-coated prism represented by the abrupt decreased of R-min to 96.50% at lambda=633nm. The SPR angle was red-shifted about 0.30 degrees throughout this region. The SPR signal getting weaker as light excitation wavelength entered the IR region (from lambda=870nm to lambda=1550nm) indicated by the 64.34% inclination of R-min. In this region, the SPR angle was remain red-shifted from theta(SPR)=44.97 degrees until theta(SPR)=46.18 degrees with the average increment of 0.31 degrees for each wavelength. It can be concluded that the usage of red laser, lambda=633nm able to enhance the maximum excitation of SPP. The remarkable outcome of this work shows the vital role of light excitation wavelength in generating strong SPR signal for various application such as sensor and optoelectronic device.